THE INFLUENCE OF GREEN ADVERTISING AND BRAND IMAGE ON PURCHASE DECISIONS AND THEIR IMPACT ON CUSTOMER LOYALTY CHIYODA LED LIGHTS (Case Study in Cisaranten Kidul Village) - Adang Sutisna (SEAN Institute, 2022)
Every customer who is loyal to a product has factors in deciding to buy. This can happen when deciding to use a product, such as a Lamp. Along with the green movement around the world to make people aware of their care for the environment, so many companies advertise their products with environmental themes or what is called Green Advertising, this makes light consumers switch to using LED lights. Brand Image is a perception of a brand that has an impact on a customer's purchase decision. Based on the description above, the writer is interested in conducting a research in the form of a thesis with the title